Genome sequencing and RNA‐seq analyses of mitochondrial complex I deficiency revealed Alu insertion‐mediated deletion in NDUFV2. Issue 11 (2nd September 2021) - Kishita, Yoshihito; Shimura, Masaru; Kohda, Masakazu; Fushimi, Takuya; Nitta, Kazuhiro R.; Yatsuka, Yukiko; Hirose, Shinichi; Ideguchi, Hiroshi; Ohtake, Akira; Murayama, Kei; Okazaki, Yasushi
Abstract: Isolated complex I deficiency is the most common cause of pediatric mitochondrial disease. Exome sequencing (ES) has revealed many complex I causative genes. However, there are limitations associated with identifying causative genes by ES analysis. In this study, we performed multiomics analysis to reveal the causal variants. We here report two cases with mitochondrial complex I deficiency. In both cases, ES identified a novel c.580G>A (p.Glu194Lys) variant in NDUFV2 . One case additionally harbored c.427C>T (p.Arg143*), but no other variants were observed in the other case. RNA sequencing showed aberrant exon splicing of NDUFV2 in the unsolved case. Genome sequencing revealed a novel heterozygous deletion in NDUFV2, which included one exon and resulted in exon skipping. Detailed examination of the breakpoint revealed that an Alu insertion‐mediated rearrangement caused the deletion. Our report reveals that combined use of transcriptome sequencing and GS was effective for diagnosing cases that were unresolved by ES.